2008
DOI: 10.1128/aem.01345-08
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium Source Tracking in the Potomac River Watershed

Abstract: To better characterize Cryptosporidium in the Potomac River watershed, a PCR-based genotyping tool was used to analyze 64 base flow and 28 storm flow samples from five sites in the watershed. These sites included two water treatment plant intakes, as well as three upstream sites, each associated with a different type of land use. The uses, including urban wastewater, agricultural (cattle) wastewater, and wildlife, posed different risks in terms of the potential contribution of Cryptosporidium oocysts to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 62 publications
(71 reference statements)
2
55
0
2
Order By: Relevance
“…A 15-month study in the Potomac River watershed that analyzed a total of 92 water samples has reported the identification of 15 Cryptosporidium species/genotypes in 50 Cryptosporidium-positive samples by PCR-RFLP and sequencing, of which C. andersoni was the most common species (41 PCR-positive samples) compared to wildlife genotypes (14 samples). C. andersoni was the species presenting the highest level of contamination inferred from the rates of PCR amplification of 5 replicates compared to the wildlife species/genotypes identified by the same study (30). Likewise, C. andersoni, C. baileyi, and the Cryptosporidium skunk genotype were predominant species in samples from the Oldman River, Canada (14).…”
Section: Discussionmentioning
confidence: 98%
“…A 15-month study in the Potomac River watershed that analyzed a total of 92 water samples has reported the identification of 15 Cryptosporidium species/genotypes in 50 Cryptosporidium-positive samples by PCR-RFLP and sequencing, of which C. andersoni was the most common species (41 PCR-positive samples) compared to wildlife genotypes (14 samples). C. andersoni was the species presenting the highest level of contamination inferred from the rates of PCR amplification of 5 replicates compared to the wildlife species/genotypes identified by the same study (30). Likewise, C. andersoni, C. baileyi, and the Cryptosporidium skunk genotype were predominant species in samples from the Oldman River, Canada (14).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, many studies have reported that C. andersoni, which is predominantly a parasite of adult cattle, C. ubiquitum, which is a common Cryptosporidium species in sheep and C. parvum are the dominant Cryptosporidium species detected in watersheds and raw and drinking water (Yang et al 2008;Ruecker et al 2007;Nichols et al 2010;Smith and Nichols, 2010). In addition, the high density of cattle and sheep across Australia, which contribute a large volume of manure to catchments indicate that they are the main species that present a risk to public health in Australian catchments.…”
Section: S P E C I E S a N D S T R A I N S O F C R Y P T O S P O R I mentioning
confidence: 99%
“…Fresh faecal samples were collected from the floor (box, terrarium) immediately after defecation and each sample was placed into a separate plastic tube without fixative. Yang et al (2008) NS -origin of the host (country) was not specified in the manuscript.…”
Section: Specimens Studiedmentioning
confidence: 99%